Integrated and enhanced dataset on food security and household coping strategies of Burkina Faso (2018-2023) - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset integrates and standardizes multiple cross-sectional household food security surveys conducted twice a year to support the Cadre Harmonisé process in West Africa. The surveys are carried out in two waves each year: